The Effectiveness of Project-Based Learning Model in Improving Student Learning Outcomes at SD Negeri 0406 Aek Tinga - Lubis, Ida Perianti; Lubis, Duma Sari (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to test the effectiveness of the Project-Based Learning (PjBL) learning model in improving student learning outcomes on the subject of Faith in the Books of Allah in Grade 6 of SD Negeri 0406 Aek Tinga. This study uses a Classroom Action Research (CAR) approach with a research design consisting of two cycles, where each cycle includes planning, implementation, observation, and reflection. The population of this study was 30 students of Grade 6 of SD Negeri 0406 Aek Tinga. The sample of this study was all students of Grade 6 selected by total sampling. The research data were obtained through instruments in the form of learning outcome tests, observations, and interviews. Data analysis was carried out using descriptive analysis and t-tests to determine significant differences between student learning outcomes before and after the implementation of the PjBL model. The results showed that the implementation of the PjBL model had a significant impact on improving student learning outcomes. This is evidenced by an increase in the average score of test results before and after project-based learning, as well as from observations that showed an increase in student involvement and motivation during the learning process. Based on the t-test, there is a significant difference between the experimental group using the PjBL model and the control group using the conventional method. The PjBL model also has a positive impact on developing students' social and collaboration skills. This study concludes that the PjBL model is effective in improving student learning outcomes on the material of Faith in the Books of Allah in Grade 6 of SD Negeri 0406 Aek Tinga. Therefore, it is recommended that the PjBL model be applied more widely in schools as an alternative to improve the quality of learning that is more active, creative, and enjoyable